Development of a multi-component tobacco cessation training package utilizing multiple approaches of intervention development for health care providers and patients attending non-communicable disease clinics of Punjab, India - Bhatt, Garima; Goel, Sonu; Grover, Sandeep; Medhi, Bikash; Singh, Gurmandeep; Gill, Sandeep Singh; Swasticharan, Leimapokpam; Singh, Rana J. (Frontiers in Public Health, 2022)
Background Providing patients with personalized tobacco cessation counseling that is culturally sensitive, and disease-specific from healthcare providers (HCPs) as part of their routine consultations is an approach that could be incorporated, using existing healthcare systems such as the Non-Communicable Disease (NCD) clinics. This paper describes the development of a multi-component culturally tailored, patient-centric, disease-specific tobacco cessation package utilizing multiple approaches of intervention development for healthcare providers and patients attending these clinics in Punjab, India, along with a proposed framework for implementation. Methods The proposed intervention package was developed in 6 stages. These included a review of literature for identifying successful cessation interventions for ethnic minority groups, co-production of the package with all stakeholders involved via a series of consultative meetings and workshops, understanding contextual factors of the state and ‘factor-in’ these in the package, pre-test of the package among HCPs and tobacco users using in-depth interviews, micro detailing and expansion of the package by drawing on existing theories of the Cascade Model and Trans-Theoretical Model and developing an evolving analysis plan through real-world implementation at two pilot districts by undertaking a randomized controlled trial, assessing implementer's experiences using a mixed-method with a primary focus on qualitative and economic evaluation of intervention package. Results A multi-component package consisting of a booklet (for HCPs), disease-specific pamphlets and short text messages (for patients; bilingual), and an implementation framework was developed using the 6-step process. A major finding from the in-depth interviews was the need for a specific capacity-building training program on tobacco cessation. Therefore, using this as an opportunity, we trained the in-service human resource and associated program managers at the state and district-level training workshops. Based on the feedback, training objectives were set and supported with copies of intervention package components. In addition, the role and function of each stakeholder were defined in the proposed framework. Conclusion Consideration of tobacco users' socio-cultural and patient-centric approach makes a robust strategy while developing and implementing an intervention providing an enlarged scope to improve care services for diversified socio-cultural communities.